Study of Halal Certification for Food and Beverage Products based on PP No. 39 of 2021 - purborini, vivi sylvia (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
Indonesia is a democratic country that is secular, and the majority of its population is Muslim. The research method used is a qualitative approach, which is research conducted directly to the subject under study, descriptive in nature, to obtain data from the problem. Halal certification is a halal certification issued by the Institute for the Assessment of Food, Drugs and Cosmetics (LPPOM-MUI) which states that a product is in accordance with Islamic law. This halal certificate can be used to make halal labels. Government Regulation Number 39 of 2021 concerning the Implementation of the Halal Product Guarantee Field is an implementing regulation that was born as a follow-up to Law Number 11 of 2020 concerning Job Creation. It should be noted that Article 48 of Law Number 11 of 2020 concerning Job Creation is the result of an amendment to the previous law, namely Law Number 33 of 2014 concerning Halal Product Guarantee. So automatically, Government Regulation Number 31 of 2019 concerning the Implementation of Halal Product Guarantee is no longer in effect and is replaced by Government Regulation Number 39 of 2021 concerning the Implementation of the Halal Product Guarantee Field.